Regulations and Ordinances, Together with a Statement of the Various Acts, Ordinances and Resolutions Concerning the Town of Salem, N.C., from 1856 to 1896, at 5, § 7 (1896) - (:unkn) unknown (General Publisher, 1896)
No person shall fire a gun or pistol for the purpose of sport or amusement, nor shoot or discharge any sling shot, or other projectile unless by written consent of the Mayor. Fine Ten Dollars for Each offense]
--
Keywords: DISCHARGE